Europe and the migration of Christian communities from the Middle East - Tamcke, Martin (Göttinger Orientforschungen, I. Reihe: Syriaca, 2022)
Cover -- Title pages -- Inhalt/Content -- Vorwort/Preface -- Martin Tamcke: The Religious Fragmentation Migrates -- Heleen Murre-van den Berg: Rewriting Global Orthodoxy -- Lars Klein: No Place for "Arabs and Turks"? -- Liubov Fadeeva, Ekaterina Burmistrova: Migration and Radical Right Movements in Europe -- Ertuğrul Şahin: Minoritäten im Islam -- Kai Merten: New Home Europe -- Jan Gehm: Microhistory of a Syriac Orthodox Community in Germany -- Matija Miličić: The Coptic Orthodox Church in the Netherlands -- Gaétan du Roy: Coptic Traditions' Digitization in Francophone Europe -- Harutyun G. Harutyunyan: Migration and Integration of Armenian-Orthodox Christiansin the Historical and Modern Diaspora -- Christopher Sheklian: "Their Compatriot St. Servatius" -- Sevgi Çilingir: The Issue of Historical Christian Minorities inEU-Turkey Relations: The Case of Armenians1 -- Martin Tamcke: Minority, Cosmopolitan, Migrant, Stateless Person? -- Habtom Yohannes: Some Reflections on the "abä-nefs" WhatsAppof an Eritrean Priest Queshi-Afwerki -- Baby Varghese: Europe and Migration of Christian Communities from India -- Leonard Stinsky et al.:Flight, Eviction and Hostage Holding of Assyrian Christiansfrom the Valley Goran -- Sinem Abka: The Integration Trajectory of Orthodox Greek Refugeesin Mainland Greece -- Natalia Zhurbina: The Integration of Russia towards the Migrant's Children: Challenges and Prospects -- Sevgi Çilingir: Challenges of Religious Conversion in an Asylum Setting -- Anhang/Appendix -- Hermann Teule: Der Stellenwert des Studiums des östlichen Christentums -- Sinem Abka: The EU's Impact on the Changing Status of Greek Minorities inTurkey - PP-Presentation -- Grußworte/Greetings -- Bischof Armash Nalbandian -- Rade Kisić -- Alla Alkushina -- Martin Tamcke: Abschiedsrede/Farewell Speech -- Martin Tamcke: Schlusswort.